2012
DOI: 10.3109/03630269.2012.747441
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Tube Multiplex Gap-Polymerase Chain Reaction for the Detection of Eight β-Globin Gene Cluster Deletions Common in Southeast Asia

Abstract: Up to now, more than 200 different β-thalassemia (β-thal) mutations have been characterized. The majority are point mutations causing expression defects. Only approximately 10.0% of the defects are caused by large deletions involving the β-globin gene cluster causing β(0)-thal, (δβ)(0)-thal, (G)γ((A)γδβ)(0)-thal and other conditions with or without persistence of fetal hemoglobin (Hb). For the prevention of severe forms of β-thal intermedia and β-thal major, it is important to identify carriers of point mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Genomic DNA was prepared from peripheral blood leukocytes using a standard method. Screening for DNA deletions causing δβ 0 ‐thalassemia and HPFH found in Thailand and other Asian countries was carried out using multiplex PCR as previously described . Identifications of α o ‐thalassemia (SEA and THAI‐deletions), α + ‐thalassemia (3.7 and 4.2 kb deletions), Hb Constant Spring and Hb Pakse' mutations are routinely performed in our laboratory using PCR methodologies described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was prepared from peripheral blood leukocytes using a standard method. Screening for DNA deletions causing δβ 0 ‐thalassemia and HPFH found in Thailand and other Asian countries was carried out using multiplex PCR as previously described . Identifications of α o ‐thalassemia (SEA and THAI‐deletions), α + ‐thalassemia (3.7 and 4.2 kb deletions), Hb Constant Spring and Hb Pakse' mutations are routinely performed in our laboratory using PCR methodologies described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…To detect the most common deletions causing alpha-and beta-thalassemia worldwide, a relatively simple, inexpensive multiplex gap-PCR is used [17][18][19][20][21]. A limitation to this otherwise excellent system is that primers can be included into the multiplex only when breakpoint sequences are known.…”
Section: The General Strate Gy For Mo Lecular Diagnostics For Hbpsmentioning
confidence: 99%
“…While only the β-globin gene is partially or completely removed in some of those deletions, the δ-globin gene or δ- and γ-globin genes are deleted in addition to the β-globin gene in some others [1,2]. It was also stated that 10% of the β-globin gene mutations are large deletions causing phenotypes associated with β-thal [3]. The phenotypes produced by deletions in the β-globin gene cluster are classified according to the gene(s) involved, such as β-thal, δβ-thal, εγδβ-thal, and hereditary persistence of fetal hemoglobin (HPFH) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite general carrier frequency for β-globin gene mutations being reported at 2% for Turkey and at as high as 10% for Antalya Province, large deletional mutations in the β-globin gene cluster have rarely been reported so far and there is no systemic study on mutation profiles of large deletional mutations in the β-globin gene cluster in Turkey [4,5,6,7,8,9]. On the other hand, the number of studies on variety and allelic frequencies of large deletions in the β-globin gene cluster has been growing recently [2,3,10,11,12]. Previous studies revealed that HPFH-1, HPFH-2, HPFH-3, Sicilian (δβ)0-thal, Chinese Gγ(Aγδβ)0-thal, Hb Lepore, Asian-Indian inversion-deletion Gγ(Aγδβ)0-thal, and Turkish inversion-deletion (δβ)0-thal mutations are among the most recurrent large deletional mutations in the β-globin gene cluster [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation